2010
DOI: 10.1007/s00414-010-0444-6
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric estimation of age in paraffin-embedded ribs: a feasibility study

Abstract: Estimation of age at death from human bones in legal medicine or in anthropology and archaeology is hampered by controversial results from the various macroscopic and histological techniques. This study attempted an estimation of age at death by histomorphometric analysis, from the fourth left rib adjacent to the costochondral joint in 80 forensic cases. Use of the picrosirius dye provided a reliable staining of the decalcified paraffin-embedded ribs. The total bone cortical area, the major and minor diameter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
5
16
0
1
Order By: Relevance
“…The validation sample within that study demonstrates that the error associated with the development sample is consistent with prior studies (Stout and Paine 1992), with a predictive interval of ±24.44 years (Cho et al, 2002). This method strongly supports a population approach to histological age‐estimation largely based on ancestry, and the variables used form the basis for more recent population specific histological age‐estimation methods (Kim et al, 2007; Pavón et al, 2010; Cannet et al, 2011). An assessment by Crowder (2005) using 215 samples derived from the known age‐at‐death Spitalfields skeletal collection found that the histological age‐estimation method developed by Cho et al (2002) accurately estimated ages within the predicted interval.…”
supporting
confidence: 58%
“…The validation sample within that study demonstrates that the error associated with the development sample is consistent with prior studies (Stout and Paine 1992), with a predictive interval of ±24.44 years (Cho et al, 2002). This method strongly supports a population approach to histological age‐estimation largely based on ancestry, and the variables used form the basis for more recent population specific histological age‐estimation methods (Kim et al, 2007; Pavón et al, 2010; Cannet et al, 2011). An assessment by Crowder (2005) using 215 samples derived from the known age‐at‐death Spitalfields skeletal collection found that the histological age‐estimation method developed by Cho et al (2002) accurately estimated ages within the predicted interval.…”
supporting
confidence: 58%
“…in limb bones. (Crowder and Rosella 2007;Cannet et al 2011). Furthermore, ribs are not subjected by default to detailed analyses during skeleton assessments, which is why interference into their integrity through cutting does not significantly affect the information value of the entire skeleton.…”
Section: Methodsmentioning
confidence: 99%
“…They suggested, however, that their method might be applied to female individuals as well. Methods by Stout and Paine (1992) and Cho et al (2002), used in this study, also involve calculations for both sexes together, as does the method by Cannet et al (2011). Data presented in Reich (1998), suggesting that separate regression equations should be determined for men and females.…”
Section: Sexual Dimorphismmentioning
confidence: 99%
See 2 more Smart Citations